"THREADS OF THOUGHT: HOW MUTAZILITE RATIONALISM AND ASHARITE ORTHODOXY WOVE THE FABRIC OF ISLAMIC PHILOSOPHY" - Mohammad Ishaq Lone (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Asharites oppose Mutazilites' views on free will. Instead, they argue that, while humans have some freedom of action and complete freedom of thought, only Allah has the ability to perform actions, whilst humans do not. Humans cannot fully comprehend notions like freedom and justice, which are exclusively the domain of God. The current study illuminates the fundamental concepts of Mutazilites and Asharites, as well as how they influenced individuals and states. Their contributions to the spread of Islam have been tremendous, leaving everlasting marks on the hearts of Muslim nations. The present research examines the influence of Mutazilite and Ashrite ideas on Muslim philosophy.